PP.02.40: RELATION OF 24-HOUR URINARY CAFFEINE AND PARAXANTHINE EXCRETIONS WITH SELF-REPORTED CONSUMPTION OF COFFEE AND OTHER CAFFEINATED BEVERAGES IN THE GENERAL POPULATION. (June 2015) - Petrovic, D.; Guessous, I.; Pruijm, M.; Ponte, B.; Ackermann, D.; Estoppey-Younès, S.; Péchère-Bertschi, A.; Paccaud, F.; Vogt, B.; Mohaupt, M.; Martin, P.; Burnier, M.; et al.
Abstract : Objective: Caffeine has been associated with many chronic disease such as high blood pressure. Caffeine intake is generaly estimated by the use of self-reported consumption of caffeine, but it is not clear how well self-reported consumption of caffeine correlates with validated method to measure caffeine intake (e.g., urinary excretion). We investigated the associations of self-reported consumption of caffeinated drinks with urinary excretion of caffeine and its major metabolite (paraxanthine). Design and method: We used data from 267 men and 280 women to the population-based Swiss Kidney Project on Genes in Hypertension (SKIPOGH) study. Caffeinated drink consumption was assessed by food frequency questionnaire, where intake frequency was self-reported through 5 categories: "Never", "1–4 beverages/month", "1–4 beverages/week", "> = 5 beverages/week", "1>= beverage/day". Physiological data was collected through medical visit and 24-h urine collection (caffeine and paraxanthine urinary excretions). Mixed linear regression was performed to test association of reported consumption of caffeinated drinks with metabolite excretions. Receiver Operating Characteristic (ROC) analysis was conducted to discriminate low vs. high caffeine exposure, defined as consuming more than 4 cups of coffee per day, or more than one beverage per day for caffeinated soft drinks and energy drinks. Results: The 24-hour urinary excretions of caffeine and paraxanthine correlated with self-reported caffeinated coffee consumption (unadjusted R2 = 0.275, P < 0.001 [Figure]) but not with the consumption of other caffeinated drinks (soft drinks, energy drinks) (unadjusted R2 = 0.027, P = 0.004) nor with the consumption of decaffeinated drinks (unadjusted R2 = 0.008, P = 0.382). Reported number cups of coffee provided high sensitivity/specificity to discriminate low vs. high caffeine exposure, (>4 cups; AUC = 0.834), whereas reported consumption of other caffeinated drinks (soft drinks, energy drinks), did not allow this discrimination (> 1 beverage; AUC = 0.535). Figure. No caption available. Conclusions: Self-report appears to be a sensitive, specific and simple way to capture exposure to caffeine. Our findings suggest that coffee was the major source of excreted caffeine and paraxanthine, whereas the contribution of other caffeinated drinks was less clear.